Beam instability stabilization in hybrid plasma waveguide - Antonov, A.N.; Kovpik, O.F.; Kornilov, E.A.; Svichensky, V.G. (Вопросы атомной науки и техники, 2005)
The authors submit the results of investigations of the beam-plasma instability derangement in the hybrid plasma waveguide. The latter, placed into the longitudinal magnetic field, consists of a chain of cavities connected inductively and its passage channel is filled with plasma. In this plasma, the excitation of low-frequency oscillations that belong to the low-hybrid resonance range is examined. The investigations are carried out in the beam-plasma oscillator. The plasma is generated and maintained due to the beam-plasma discharge. Приведені результати дослідження зриву пучково-плазмової нестійкості у гібридному плазмовому хвилеводі, розміщеному в поздовжньому магнітному полі, що складається з ланцюга індуктивно зв’язаних резонаторів, пролітний канал якого заповнений плазмою, при збудженні низькочастотних коливань в його плазмі із області нижнєгібридного резонансу зовнішнім генератором. Гібридний плазмовий хвилевід використовується в пучково-плазмовому генераторі. Плазма створюється і підтримується за рахунок пучково-плазмового розряду. Приведены результаты исследования срыва пучково-плазменной неустойчивости в гибридном плазменном волноводе, помещенном в продольное магнитное поле, состоящем из цепочки индуктивно связанных резонаторов, пролетный канал которой заполнен плазмой, при возбуждении низкочастотных колебаний в его плазме из области нижнегибридного резонанса внешним генератором. Гибридный плазменный волновод используется в пучково-плазменном генераторе. Плазма образовывается и поддерживается за счет пучково- плазменного разряда. The authors are grateful to A.P. Tolstolugsky for the
calculation of the spiral aerial, loaded with plasma and to
L.D. Lobzov for the oscillator adjustment. S.S.
Pushkarev’s help in the elaboration of the technique of
registering the probing pulses in plasma with probes is
gratefully acknowledged. We also wish to thank V.A.
Buts for the discussion of the results and valuable
suggestions in the course of the work fulfillment.